A Re-evaluation of Whether Non-monosynaptic Homonymous H Reflex Facilitation Tests Propriospinal Circuits - Fisher, Karen M.; Baker, Stuart N. (Frontiers in Systems Neuroscience, 2021)
The C3-C4 propriospinal system is an important pathway mediating movement in cats; it contributes to movements in primates (including humans), and may have a role in recovery after lesion. Validated clinical tests of this system would find many applications, therefore we sought to test whether non-monosynaptic homonymous facilitation of the forearm flexor H reflex is mediated solely via a C3-C4 propriospinal pathway. In one anaesthetised macaque monkey, median nerve stimulation elicited an H reflex in the flexor carpi radialis (FCR). Median nerve conditioning stimuli at sub-threshold intensities facilitated the H reflex, for inter-stimulus intervals up to 30 ms. Successive spinal surgical hemisections were then made. C2 lesion left the homonymous facilitation intact, suggesting mediation by spinal, not supraspinal pathways. Facilitation also remained after a second lesion at C5, indicating a major role for segmental (C7-C8) rather than propriospinal (C3-C4) interneurons. In separate experiments in five healthy human subjects, a threshold tracking approach assessed changes in peripheral axon excitability after conditioning stimulation. This was found to be enhanced up to 20 ms after the conditioning stimulus, and could partly, although not completely, underlie the H reflex facilitation seen. We conclude that homonymous facilitation of the H reflex in FCR can be produced by segmental spinal mechanisms, as well as by a supernormal period of nerve excitability. Unfortunately, this straightforward test cannot therefore be used for selective assessment of propriospinal circuits.